The Validity of Learning Media Using Aurora 3D Presentation Application Equipped with a Guidebook on Animalia Material for Student of Grade X SMA - Anggun Sepri Yenti; Relsas Yogica; Armen Armen; Sa'diyatul Fuadiyah (Universitas Negeri Padang, 2020)
Technological progress is very rapid nowadays requires creative and innovative teachers to use technology to design Biology learning. The teacher is expected to be able to use multimedia in learning. Besides powerpoint, other applications such as Aurora 3D Presentation. Aurora 3D Presentation is a very interesting presentation. Most teachers don't know how to use this application, so teachers and students need a manual. The purpose of this study is to create the Aurora 3D Presentation application as a learning medium for high school students. This research is research and development (R & D) research that uses the Instructional Development Institute (IDI) method. This research is 2 Biology Department lectures from FMIPA UNP and 1 Biology High School teacher. The results of this study have a valid category with 89%. This Prezi application has valid values in the aspects of content, language, presentation and graphic aspects. This means the Aurora 3D Presentation application makes it easy for middle school students.